Disentangling relationships between Alzheimer's disease plasma biomarkers and established biomarkers in patients of tertiary memory clinics - Bluma, M; Chiotis, K; Bucci, M; Savitcheva, I; Matton, A; Kivipelto, M; Jeromin, A; De Santis, G; Di Molfetta, G; Ashton, NJ; Blennow, K; Zetterberg, H; et al. (Elsevier, 2025)
Background Several plasma biomarkers for Alzheimer's disease (AD) have demonstrated diagnostic and analytical robustness. Yet, contradictory results have been obtained regarding their association with standard diagnostic markers of AD. This study aims to investigate the specific relationship between the AD biomarkers currently used in clinical practice and the plasma biomarkers.
Methods In a memory clinic cohort, we analysed plasma pTau181, pTau217, pTau231, respectively, GFAP, NfL, CSF pTau181, Aβ-PET scans, and MRI/CT visual read of atrophy. We utilized methods based on multiple linear regression to evaluate the specific associations between clinically used and recently developed plasma biomarkers, while also considering demographic variables such as age and sex.
Findings Although plasma pTau181, pTau217, pTau231, and GFAP were significantly associated with both Aβ-PET and CSF pTau181, Aβ-PET explained more variance in the levels of these biomarkers. The effect of CSF pTau181 on plasma GFAP and pTau181 was completely attenuated by Aβ-PET, whereas pTau231 and pTau217 were affected by both Aβ-PET and CSF pTau181 levels. Unlike these biomarkers, increased NfL was rather indicative of brain atrophy and older age. Based on the effect sizes, plasma pTau217 emerged as highly effective in distinguishing between A+ and A-, and T+ and T- individuals, with 60% of variance in plasma pTau217 explained by clinical AD biomarkers.
Interpretation Amyloid burden primarily drives the changes in plasma pTau181, pTau217, pTau231, and GFAP. In contrast to plasma pTau217, a significant portion of variance in plasma pTau181, pTau231, GFAP, NfL remains unexplained by clinical AD biomarkers.
Funding This research is supported by the Swedish Research Council VR: 2017-06086, 2020-4-3018, 2024-2027; Swedish Brain Foundation, Swedish Alzhzeimer Foundation, CIMED Region Stockholm/Karolinska Institutet; the Region Stockholm - Karolinska Institutet regional agreement on medical training and clinical research (ALF), Fondation Recherche sur Alzheimer (France).